Penggunaan Pakan Komplit Berbasis Limbah Industri Pertanian Terhadap Produktivitas Ternak Sapi Potong di Kabupaten Boyolali - Hanifa, Aqni; Sari, Ayu Intan (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2015)
This activity aims to increase the productivity of cattle in farms of the people through improvement of feed. This event was held in the village whole observatories, District Selo, Boyolali. Proximate analysis carried out in the laboratory feed and Nutrition, Husbandry Program, Faculty of Agriculture UNS. The material used is a member Gapoktan Sari Bumi Handayani and KTT Lembu Suro, cattle weighing 269.50 ± 31,44 kg and feed. Green feed such as rice straw and concentrate (P0, P1 and P2). The method used is 1) a discussion and interviews using a structured questionnaire, 2) technology training and extension activities preparation of cattle feed and feeding management of livestock with FGD (Focus Group Discussion), 3) Method of pilot maintenance beef cattle feedlots system for 1 month. The parameters measured were feed intake, Added Daily Body Weight (PBBH), Feed Conversion Ratio (FCR) as well as the cost of revenue and 4) monitoring activities. The collected data is then analyzed and presented descriptively. The results obtained activity 1) the involvement of members of the two groupstotaling 22 people (18 men and 4 women) and the majority (55%) aged 41-50 years in counseling and training activities, 2) the level of knowledge and skills of farmers before and after activity increased (the results of the pre test and post-test of 4,91 to 8,04), 3) obtained two kinds of concentrate applied to pilot the maintenance of beef cattle, 4) monitoring the pilot obtained feed consumption for P0, P1 and P2 are respectively 206,08; 282,92 and 245,52 kg. PBBH to P0, P1 and P2 are respectively 0,80; 1,23 and 0,98 kg. FCR for P0, P1 and P2 are respectively 9,16; 8,20 and 8,93. Cost of revenue for the P0, P1 and P2 respectively is Rp 485.300,00; Rp 654.880,00; Rp 403.871,00 per head per month. The conclusion drawn is concentrate feed 1 (P1) is the best feed for optimizing the productivity of cattle. Keywords: complete feed, beef cattle productivity, farm people, Boyolali